Fe3O4 nanoparticle-modified multi-walled carbon nanotubes for the determination of synthetic pyrethroids in human blood - Cui Yanhua; Shen Weidong; Yang Fan; Pan Yaoyue; Zhang Suling; Yao Weixuan (Wolters Kluwer Medknow Publications, 2019)
In this study, a sensitive and rapid magnetic solid-phase microextraction (MSPE) procedure based on Fe3O4 nanoparticle-modified, multi-walled carbon nanotubes combined with a gas chromatography/electron capture detector (GC/ECD) was developed to quantify pyrethroids in human blood samples. This study compared liquid-liquid extraction and solid-phase extraction methods and found that the MSPE-GC/ECD method had many advantages, such as high recovery rate, high extraction efficiency, high detection sensitivity, low limit of detection, and simple operation. It can meet the actual requirements for the determination of synthetic pyrethroids in human blood.